Modalities of treatment for sleep disordered breathing - Tin, Win; Ohn, Khin Maung (Asian Journal of Medical and Biological Research, 2016)
Sleep disordered breathing is a spectrum of diseases that includes snoring, upperairway resistance syndrome and obstructive sleep apnea. It occurs more in obese males, resulting in hypertension and cardiac complications if untreated. There are various treatments, conservatively and surgically, starting from simple tonsillectomy to multi-level surgeries and multi discipline. Literature review was carried out on the pathophysiology, clinical presentation, complications, diagnosis and various treatments, using internet Google, search PubMed. Additional information was obtained by cross referencing, using text and journals in the medical libraries. Asian J. Med. Biol. Res. September 2016, 2(3): 361-369